IS/IT investment evaluation and benefits realization issues in a government organisation - Lin, Chad; Pervan, Graham (Southern Cross University, 2001)
debate in the IS/IT literature amongst researchers, academics, and practitioners. This is as true in Australia as it is in the rest of the developed world. Thus, a detailed program of research into the current Australian practice and processes of IS/IT investment evaluation and benefits realisation was initiated. As part of this research program an in-depth case study of these practices and processes in a large government department, with a mix of insourced and outsourced IS/IT activities, was conducted. Issues arising from the study include a lack of a formal IS/IT investment evaluation methodology and a lack of understanding of the evaluation approach used, a lack of any (formal and informal) benefits realisation methodology and a lack of understanding of benefits management practices, the use of an informal IS/IT investment evaluation process, focus on quantitative IS/IT investment evaluation measures, conflicting motivations for outsourcing, different perception of success of the contracts by stakeholders, IS/IT skill shortage within the organisation, embedded contract mentality, complicated contract arrangements, over-reliance on a single contractor, lack of user involvement/participation in contract development, and general lack of commitment by contractors.